Possibilidades formativas das HTPC'S: um olhar a partir de professores polivalentes - Innocenti, Thamirys Desirée (2016)
This study aimed to investigate which are the formative possibilities developed in the Collective Pedagogical Work Time (HTPC, in Portuguese) of a public school located in Baixada Santista region and understand how the training possibilities are in the HTPC¿s having as research subjects polyvalent teachers in the early years of elementary school. Initially, a literature and document research was performed in order to find data that subsidize the training, social, and legal issues associated with the theme. The research, along its process showed that this is a case study, focusing on their study of the HTPC¿s. For this, we used the theoretical support of researchers like Fusari, Charlot, Nóvoa, Imbernón, Garcia, Sacristan, Pimenta, Franco, Ghedin, Libâneo, Silva Junior, among others. The field research was developed through a qualitative approach, and data collection; we used the technique of observation, guided by Vianna, held in March and May 2015 in a total of seven comments in morning, intermediate and evening periods. The survey data showed limits and training opportunities present in the space/time of HTPC¿s. The limits found in HTPC¿s were regarding: the chronological time used for their realization; the absence of Technical and Pedagogical Team; and the interaction of polyvalent teachers in HTPC¿s. The formative possibilities were presented in three categories: HTPC as space/time for listen; HTPC as space/time for training; HTPC as space/time of exchange of experience/knowledge.